2020
DOI: 10.1109/access.2020.3039639
|View full text |Cite
|
Sign up to set email alerts
|

Automated Non-Intrusive Load Monitoring System Using Stacked Neural Networks and Numerical Integration

Abstract: Population growth and new consumer needs, among other factors, have lead to growing energy demand, without a concomitant increase in energy generation. This way, reduction and rationalization of energy consumption, especially by residential users, have become a global concern generating a need for developing techniques for efficient management and distribution of the available energy. Non-Intrusive Load Monitoring (NILM) techniques have provided valuable information about energy consumption for power generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…If a faster communication speed is required, the 4G/3G (such as SIM7600CE shield for Arduino, which supports 4G, 3G, and GPRS data transmission) module can be employed. [13]. They employed REDD and UK-DALE datasets and achieved F1-scores of 0.879 and 0.858, respectively, for the datasets.…”
Section: B Implementation Cost and Execution Timementioning
confidence: 99%
See 1 more Smart Citation
“…If a faster communication speed is required, the 4G/3G (such as SIM7600CE shield for Arduino, which supports 4G, 3G, and GPRS data transmission) module can be employed. [13]. They employed REDD and UK-DALE datasets and achieved F1-scores of 0.879 and 0.858, respectively, for the datasets.…”
Section: B Implementation Cost and Execution Timementioning
confidence: 99%
“…However, the increasing computational complexity associated with the growing number of appliances makes the methods difficult to implement for real-time applications. Individual appliance identification using features of the low-frequency power-series signal was demonstrated by Corrêa et al [13] and Zhang et al [14]. Rafiq et al also identified a single appliance using low-frequency active power (P), apparent power (S), reactive power (Q), rms voltage (V), rms current (I), and power factor (PF) data [15].…”
Section: Introductionmentioning
confidence: 99%